Exploring Junior High School Student’s Experiences in Learning English Conversation through Drama, English Camp, and Tourism - Refi Regita Sari; Aryati Prasetyarini (LPPM Universitas Advent Indonesia, 2025)
Drama, English Camp, and Tourism are considered effective strategies for improving students' conversational skills in secondary schools. However, studies exploring the integration of these three approaches are still limited. Addressing this gap, the present study aims to explore students’ experiences in an innovative English learning program, specifically through Drama (English Performance), English Camp, and Edutrip (Tourism), and to identify the benefits and challenges encountered in improving their speaking skills. The study is driven by students’ low interest and lack of self-confidence in speaking English in conventional classroom settings, highlighting the need for innovative and engaging learning environments. This research employed a qualitative method with a case study design. Data were collected through interviews and documentation involving six students from a global class at one Muhammadiyah junior high school in Surakarta who participated in the English Conversation Program. Data were analyzed using the Miles and Huberman model, including data reduction, display, and conclusion drawing. The findings show that the English Conversation Program offered enjoyable and contextual learning experiences, improving students’ confidence, fluency, pronunciation, and spontaneous speaking ability. The main challenges faced included pronunciation difficulties, anxiety, and limited vocabulary, which were addressed through self-practice, peer collaboration, and vocabulary preparation. This study highlights the importance of experiential learning in enhancing students’ English speaking skills.